Quasinormal Modes of Bardeen Black Hole in 5-Dimensional Gauss–Bonnet Gravity - Feng-Miao Ge; Bingyuan Wei (Advances in High Energy Physics)
This study addressed the scalar field quasinormal ringing behavior of black holes. We investigated scalar field perturbations in Bardeen black hole spacetime in 5-dimensional Einstein–Gauss–Bonnet (EGB) gravity. Using the sixth-order Padé approximation and the finite difference method, we computed the frequency of quasinormal modes (QNMs) in the spacetime background. The calculations demonstrated that the real part of the QNMs ω increased, whereas the imaginary part decreased with increase in the magnetic charge parameter Q of the Bardeen black hole for a fixed Gauss–Bonnet parameter α. This was also valid when Q was fixed and α increased, where in the real part of the QNMs increased and the absolute value of the imaginary part decreased. However, the change in the latter case was more significant than that in the former; thus, the frequency of eigenvibration of this black hole background under the scalar field perturbation increased and the decay of eigenvibration decreased with increase in α or Q2. Moreover, this result shows that the effect of α on the intrinsic vibration of this black hole was greater than that of Q.